1996
DOI: 10.1007/s0021663560027
|View full text |Cite
|
Sign up to set email alerts
|

A simple and versatile PSA system for heavy metal determinations

Abstract: An easy to build potentiometric stripping analysis system for heavy metal determinations (Zn, Cd, Pb, Cu) is described which reaches good sensitivity and precision. Main components are an IBM compatible computer, an ADDA-conversion card and two selfmade electrodes, so it can be realized for one tenth of the price of complete commercial systems. A graphite pencil lead covered with a Hg-film is used as working electrode and a Ag/AgCl electrode as a combined reference/counter electrode. Reproducibility and calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The electrical contact between the electrode and the instrument was realized through a metal wire wrapped at the other end of the pencil lead. Bund et al [ 70 ] described a PGE developed by connecting a silver wire to the graphite lead and the whole system was introduced through a silicon rubber into a glass tube so that the lead can be pushed out and its surface renewed by polishing before each recording. For clozapine analysis in human plasma a microsystem consisting of a micropipette tip was obtained by inserting the electrodes, with PGE as working electrode, through a septum [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrical contact between the electrode and the instrument was realized through a metal wire wrapped at the other end of the pencil lead. Bund et al [ 70 ] described a PGE developed by connecting a silver wire to the graphite lead and the whole system was introduced through a silicon rubber into a glass tube so that the lead can be pushed out and its surface renewed by polishing before each recording. For clozapine analysis in human plasma a microsystem consisting of a micropipette tip was obtained by inserting the electrodes, with PGE as working electrode, through a septum [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…PGEs were pretreated potentiostatically by maintaining the electrode in an electrolyte for more than 30 s at a selected potential higher than 1.3 V [ 9 , 53 , 55 , 56 , 60 , 70 , 99 101 , 105 , 192 , 193 ] or by scanning the potential at a given scan rate, for a certain number of cycles within a large potential range [ 2 , 57 , 58 , 61 , 69 , 103 , 106 , 188 , 194 ]. Some papers report a comparison between the two mentioned activation procedures and depending on the electrochemical performances obtained for the investigated analyte one of them was selected; for example, chronoamperometric activation of PGE was used for alkylphenols [ 50 ] and tannic acid [ 51 ] analysis and cyclic voltammetric activation of PGE for dopamine [ 21 ] and bisphenol A [ 54 ] detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature describes many applications of GRC electrodes: for determining the titratable acidity in vinegar [3,4]; in abrasive stripping voltammetry [5]; in determination of ozone [6], dopamine [7], caffeine [8], trepibutone [9], uric acid [10]; in simultaneous determination of nitrite, dopamine and serotonin [11]; as substrate for mercury [12] and bismuth [13] films in trace metal determination; in liquid chromatography for determination of phenols [14]; applied with modified surface for determination of 2,4-dichlorophenol [15]; in voltammetry of microparticles [16]; in studies of copper-chelating properties of flavonoids [17]; in studies of DNA hybridization [18][19][20][21]; for discrimination of herpes type [22]; in detection of hepatitis B virus DNA [23,24] and in studies of interaction between DNA and lycorine [25], arsenic trioxide [26] and cis-DDP [27] molecules.…”
Section: Introductionmentioning
confidence: 99%
“…It is advantageous when redox couples exhibit sluggish electrochemical charge transfer kinetics but rapid chemical charge transfer 34 and can be implemented by using straightforward equipment such as a three-electrode cell, a highimpedance operational amplifier, an x-t recorder and a potentiostat. [35][36][37] In addition, times can be measured more readily and precisely than micro currents and no potential ramp need be used (in contrast to ASV), which results in lower instrumental costs. Some workers have reported that PSA is much less affected by surface-active substances 33,[38][39][40] than are other stripping techniques, such as ASV.…”
mentioning
confidence: 99%